(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2023)
The purpose of this study was to determine the effect of price and promotion on the purchase of precious metals at PT Pegadaian (Persero) Banjarmasin partially and simultaneously as well as the dominance of the influence between price and promotion on purchase. This type of research is quantitative. The research population is the customers of PT Pegadaian Banjarmasin. The sample is 100 respondents. Quantitative descriptive data analysis technique with SPSS version 2. The results of the study show that prices do not affect the purchase of precious metals, or the effect is not significant on the purchase (Y). This is because the price of precious metals is almost the same in every seller. So, the price is very difficult to use as a competitive tool, while promotion (X2) has a significant positive effect on purchases (Y). Consumers need complete and convincing information that purchasing precious metals at Pegadaian provides many conveniences and advantages compared to other sellers. Appropriate promotions (current) such as Tik-Tok are one of the motivations for consumers to buy.